McNeill, John R; Pádua, José A. e Rangarajan, Mahesh. Environmental History: as if nature existed. New Delhi, Oxford University Press, 2010, 240 p. - Sedrez, Lise Fernanda (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2011)
Resenha de McNeill, John R; Pádua, José A. e Rangarajan, Mahesh. Environmental History: as if nature existed. New Delhi, Oxford University Press, 2010, 240 p.